Effects of blanching and drying on the production of polyphenols rich cocoa beans and product quality - Santhanam Menon, Abhay (2017)
The high potential of health beneficial polyphenols and antioxidants in cocoa beans has been a major topic for research in recent years. The large-scale application of cocoa beans for health beneficial compounds is relatively unexplored and it needs to be widely utilized by pharmaceutical and nutraceutical industries. Processing methods such as fermentation and drying are major deterrents for recovering high polyphenols in cocoa beans.